**v**= -6i + 5j ||**v**|| = | -6i + 5j | = √[(-6)² + (5)²] = √61 Unit**v**ector =**v**/ ||**v**|| = (-6i + 5j) / √61 or (-6/√61)i + (5/√61)j Hope this helps! J3 Answers · Science & Mathematics · 01/05/2012

Recall that if any vector that is a scalar multiple of

**v**has the same direction as**v**. In the case of making a unit vector...4 Answers · Science & Mathematics · 01/12/2012

cross multiply you get -3

**v**(**v**∧2-4**v**+4) = -24(**v**-2) di**v**ide both sides by -3 ==>**v**(**v**∧2-4**v**+4) = 8(**v**-2) ==>**v**^3 - 4**v**^2 +4**v**= 8**v**- 16 ==>**v**^3 - 4**v**^2 +4**v**- 8**v**+16 = 0 ==>**v**^3 - 4**v**^2 - 4**v**+16 = 0 now sol**v**e using calculator or factor theorem let f(**v**...5 Answers · Science & Mathematics · 19/06/2011

||

**v**|| = √((3)² + (-5)²) = √(9 + 25) = √34 ||w|| = √((-2)² + (3)²) = √(4 + 9) = √13 ||**v**|| - ||w|| = √34 - √13 ≈ 2.22542 Answers · Science & Mathematics · 14/03/2013

||

**v**|| = sqrt(x^2 + y^2). Square the x and y components. Add. Take the square root. Do the same with w to get ||w||. ||**v**|| - ||w|| means take the value of ||**v**| and the value of ||w|| and subtract. "...1 Answers · Science & Mathematics · 08/07/2013

lim

**V**, m-->∞ =?**V**= [mg / c] [1 - e^(-ct)/m)] = g* [1 - e^(-ct)/m)] / [c / m] (0/0) form ------(1) let c / m = k**V**= g* [1 - e^-kt] / [k] -------------------------------------------------- e^-kt = 1 - kt + (kt...4 Answers · Science & Mathematics · 04/04/2007

**v**^4 + 9v^3 - 13v^2 - 213v - 360 = 0 You start by testing out values...6's, 9's and also a few negative signs, so I will test out**v**= -3: (-3)^4 + 9(-3)^3 - 13(-3)^2 - 213(-3) - 360 = 81 - 243 - 117 + 639 - 360 = 720...2 Answers · Science & Mathematics · 11/11/2012

IIvII is the magnitude of a vector. 1)

**v**= -5i +12j - Disregard the i and j and focus on the numbers. therefore...2 Answers · Science & Mathematics · 19/02/2008

-2/(2

**v**+4) - 3 = -6/(**v**+2) You need to find the lowest common denominator, or... the same as 3/1 Your third terms denominator is**v**+ 2 Since both 1 &**v**+ 2 both go into 2v + 4, 2v + 4 is the ...2 Answers · Science & Mathematics · 18/01/2011

p = 1 / [ √(1 - (

**v**^2/c^2)) ] p [ √(1 - (**v**^2/c^2)) ] = 1 squaring on both sides to get rid of the sq.root p^2 (1- (**v**^2/c^2)) = 1 1 - (**v**^2/c^2) = 1 / p^2**v**^2/c^2 = 1 - (1/p^2)**v**^2 = c^2...3 Answers · Science & Mathematics · 15/05/2008